Preparation method of composite thermal insulation material

By adopting a composite thermal insulation material with a multi-layer structure in a pneumatic thermal environment, combined with expanded fireproof coatings, metal titanium foils, basalt fiber-reinforced aerogel felts and phase change materials, the problems of large weight and poor stability of the thermal insulation and protection structure in the prior art are solved, and efficient thermal insulation and fire resistance and long-term stability are achieved.

CN119910986AActive Publication Date: 2025-05-02SOUTHWEST TECHNICAL ENGINEERING RESEARCH INSTITUTE OF CHINA SOUTH IND GROUP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510238474.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2025-05-02
Estimated Expiration
2044-08-22

AI Technical Summary

Technical Problem

The prior art is difficult to provide a thermal insulation and protective structure with both thermal insulation and fire protection functions, light weight, thin thickness, and long-term stability in pneumatic thermal environments.

Method used

A method of preparing a composite heat insulation material is adopted, which consists of an anti-ablation layer, a transition layer, a heat-surface protection layer, a heat-resistant layer, and a cold-surface protection layer. Among them, the ablation layer uses expanded fire-resistant coating, the transition layer uses epoxy primer, the thermal surface protection layer uses metal titanium foil, the thermal insulation layer uses basalt fiber-reinforced silica aerogel felt, the thermal resistance layer uses phase change material, and the cold surface protection layer is metal titanium foil.

Benefits of technology

It has achieved composite materials with excellent thermal insulation and fire resistance, light weight, thin thickness and good long-term stability. It can be effectively used for thermal protection of high-speed aircraft such as missiles and is suitable for high-temperature environments of 400℃ to 1200℃.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119910986A_ABST
    Figure CN119910986A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a composite thermal insulation material, and relates to the field of fireproof thermal insulation materials, the thermal insulation composite material sequentially comprises an anti-ablation layer, a transition layer, a hot surface protection layer, a thermal insulation layer, a thermal resistance layer and a cold surface protection layer; the method comprises the following specific steps: step 1, preparing coatings or blanks of all layers, and cutting the blanks; secondly, the heat insulation layer and the heat resistance layer are sequentially attached to the end face of the hot face protection layer, and then a weldment composed of the hot face protection layer, the heat insulation layer and the heat resistance layer is embedded into the cold face protection layer and welded; and thirdly, the surface of the hot face protection layer is coated with a transition layer, then the surface of the transition layer is coated with an anti-ablation layer through a multi-time coating technology, and the anti-ablation anti-corrosion coating is obtained. The composite material obtained by the method not only has the characteristics of excellent fireproof and heat-insulating properties, small thickness, light weight, good long-term stability and the like, but also has the advantages of simple structure, convenience in installation, wide application range and the like.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention is a divisional application of patent application number 202411158584.5, and the invention name is “An integrated thermal insulation composite layer and its preparation method”. Technical Field

[0002] The invention relates to the technical field of fireproof and heat-insulating materials, and in particular to a method for preparing a composite heat-insulating material. Background Art

[0003] Aerodynamic thermal environment refers to the complex thermal environment caused by the violent aerodynamic interaction between an object and the surrounding air during high-speed movement. Aerodynamic heat will not only cause the surface temperature of the aircraft to rise sharply, causing the strength and stiffness of the aircraft's outer wall to decrease, but it will also easily affect the internal components of the aircraft through heat transfer, causing the aircraft to be unable to operate normally. Therefore, in order to avoid the impact of the aerodynamic thermal environment, during the research and development and design process of high-speed aircraft such as missiles, it is usually necessary to set up a thermal insulation protection structure on its surface, which not only achieves thermal insulation protection and ensures the stability of the aircraft's inner cavity, but also effectively avoids the impact of high-temperature environments such as accidental fires during operation. Traditionally, the heat insulation protection structure for the surface of aircraft mainly adopts the heat insulation layer method such as fiber felt coating and protective coating spraying. However, the coated fiber felt is in the aerodynamic thermal environment for a long time, which not only has the problems of heavy weight and high space occupancy rate, but also has the problems of large ablation retreat, poor long-term stability, and poor heat insulation performance, which cannot meet the needs of long-term flight operations of aircraft such as missiles in the aerodynamic thermal environment; although the spraying protective coating can reduce the weight and space occupancy rate to a certain extent, it is in the aerodynamic thermal environment for a long time, and it is easy to smoke, slag, crack, and fall off and peel off due to low bonding strength. It is very easy to fail, causing the protective coating to lose its protective effect on the surface of the aircraft, and then causing the aircraft to be directly exposed to the aerodynamic thermal environment. It can be seen that the existing technology still lacks a heat insulation protection structure that has both heat insulation and fire prevention functions, light weight, thin thickness, and good long-term use stability for being in the aerodynamic thermal environment for a long time. Summary of the invention

[0004] In view of the problems existing in the above-mentioned prior art, the object of the present invention is to provide a method for preparing a composite thermal insulation material. The composite material prepared by this method has the advantages of good thermal insulation and fireproof performance, light weight, thin thickness, good long-term stability, easy installation, etc., and can be effectively used for thermal protection of the outer walls of high-speed aircraft such as missiles.

[0005] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a composite thermal insulation material, the thermal insulation composite material sequentially comprising an anti-ablation layer, a transition layer, a hot surface protection layer, a thermal insulation layer, a heat-resistant layer and a cold surface protection layer; wherein the anti-ablation layer adopts an intumescent fire retardant coating, the transition layer adopts a primer, the hot surface protection layer and the cold surface protection layer adopt metal titanium foil, the thermal insulation layer adopts an aerogel felt, and the heat-resistant layer adopts a phase change material; The specific preparation method is as follows: step 1, prepare coatings for the anti-ablation layer and transition layer and blanks for the hot surface protection layer, thermal insulation layer, heat-resistant layer and cold surface protection layer as needed, and cut the blanks; step 2, place the hot surface protection layer on a workbench plane, and attach the thermal insulation layer and the thermal resistance layer to the end face of the hot surface protection layer in sequence; then, embed the weldment consisting of the hot surface protection layer, the thermal insulation layer and the thermal resistance layer into the cold surface protection layer, and then fold the outer circle of the hot surface protection layer inward to form a coating for the cold surface protection layer, and weld their joints (i.e., between the hot surface protection layer and the cold surface protection layer); step 3, first apply the transition layer on the surface of the hot surface protection layer (i.e., the side away from the thermal insulation layer); then, apply the anti-ablation layer on the surface of the transition layer using a multiple-brushing process to obtain a thermal insulation composite material.

[0006] Based on the further optimization of the above scheme, the thickness of the anti-ablation layer is 0.6-1.0 mm; the intumescent fire retardant coating includes a film former, a flame retardant and a functional filler, and the mass ratio of the film former, the flame retardant and the functional filler is 2-3:6-10:1-3; wherein the film former is a high elastic polyurethane polymer (wherein the high elastic polyurethane polymer is polymerized by one or two of polycaprolactone diol and polyether diol and aliphatic polyisocyanate HDI); the flame retardant is composed of ammonium polyphosphate, pentaerythritol and melamine, and the mass ratio between them is 5-8:4-7:2-4; the functional filler is composed of nano-aluminum hydroxide, expanded graphite and ultrafine ceramic hollow microspheres, and the mass ratio between them is 5-10:2-5:3-8. The particle size of the ultrafine ceramic hollow microspheres is 20-50 μm, and the melting point is not less than 1600°C.

[0007] The flame retardant composed of ammonium polyphosphate, pentaerythritol and melamine is combined with a film-forming material to expand and carbonize in a high-temperature environment to form a dense carbonized layer, thereby achieving the purpose of heat insulation and fire prevention; at the same time, functional fillers composed of nano-aluminum hydroxide, expanded graphite and ultra-fine ceramic hollow microspheres are used to, firstly, use nano-aluminum hydroxide to inhibit the amount of smoke and reduce material loss during the high-temperature carbonization process, secondly, enhance the strength of the carbonized layer through nano-aluminum hydroxide, and thirdly, fill the gaps in the expanded carbonized layer through expanded graphite and ultra-fine ceramic hollow microspheres, thereby enhancing the heat insulation performance of the carbonized layer.

[0008] Based on further optimization of the above solution, the thickness of the transition layer is 40 to 60 μm, and the transition layer adopts epoxy primer; the bonding strength between the anti-ablation layer and the hot surface protection layer is improved by the transition layer.

[0009] Based on the further optimization of the above scheme, the thickness of the hot surface protection layer (when the hot surface protection layer is flat) is 0.03-0.1 mm; the hot surface protection layer adopts a metal embossed titanium foil structure, that is, protrusions distributed in an array are arranged on the surface of the flat titanium foil structure; the shape of the protrusions is any one of rice grains, pearls, and water droplets; the diameter of the protrusions is 1-2.5 mm, and the height is 0.4-1.0 mm; the distance between two adjacent protrusions is 4-8 mm; the number of protrusions per unit area in the hot surface protection layer is 1.5x10 4 ~6x10 4 Through the setting of the protrusions on the hot surface protection layer, firstly, the strain hardening effect generated during the pressing process of the protrusions is used to improve the stiffness of the hot surface protection layer; secondly, the roughness of the transition layer corresponding to the hot surface protection layer is increased through the distribution of the protrusions, and then the interface bonding force between the hot surface protection layer and the anti-ablation layer is increased by using the transition layer; thirdly, by preparing the protrusions and reducing the wrinkles formed during the forming process of the protective layer, the weak points of failure are reduced, the damage of the protective layer is avoided, and the overall liquid penetration resistance of the composite structure is improved; fourthly, the protrusions provide a buffer gap for the anti-ablation layer to ensure that the anti-ablation layer completes expansion and carbonization while avoiding the anti-ablation. The first is to prevent the layer from cracking and peeling due to the impact force generated by expansion; the second is to convert the reflective surface from mirror reflection to dot matrix diffuse reflection through uneven protrusions, thereby expanding the heat reflection area and improving the reflection efficiency; the third is to utilize the continuous uneven protrusions to cooperate with the thermal insulation layer to form a plurality of cavity matrices, thereby changing the interlayer flow field and forming micro air gaps, effectively blocking heat conduction, inhibiting heat convection, and improving the thermal insulation effect; the fourth is to achieve point contact between the hot surface protection layer and the thermal insulation layer, thereby reducing heat conduction between the hot surface protection layer and the thermal insulation layer, so that the heat is effectively dissipated in the cavity matrix, further improving the thermal insulation effect.

[0010] Based on further optimization of the above scheme, the thickness of the thermal insulation layer is 2 to 5 mm, and the thermal insulation layer adopts basalt fiber reinforced silica aerogel felt; wherein, the diameter of the basalt fiber is not greater than 6 μm, the mass ratio of basalt fiber to silica aerogel is 1:0.78 to 1, and the thermal conductivity of the basalt fiber reinforced silica aerogel felt at room temperature is 0.017 to 0.020 W / (m•K). Using small diameter basalt fibers as reinforcing fibers for nanoporous silica aerogel can effectively limit the solid heat conduction of the fibers themselves, making the basalt fiber felt itself have a lower thermal conductivity. At the same time, using short diameter basalt fibers to form a low volume density preform can further reduce its volume density while ensuring the mechanical properties of the fiber-reinforced aerogel composite material. The diameter of the fiber preform is close to the wavelength of near-infrared radiation, which can produce a strong diffraction and scattering effect on the near-infrared radiation, thereby further enhancing the high-temperature infrared radiation heat conduction barrier effect. In addition, the addition of basalt fibers can effectively solve the problems of pure aerogel being brittle and easy to break. The volume density of the basalt fiber reinforced silica aerogel felt is 150-170 kg / m 3 The bulk density of the preform formed by basalt fiber is 80~90kg / m 3 The density of silica aerogel is 70~80kg / m 3 .

[0011] Based on the further optimization of the above scheme, the thickness of the heat-resistant layer is 2-5 mm; the phase change material is composited by a phase change raw material and a matrix material, the phase change raw material is a microcapsule, the particle size of the microcapsule is 10-100 μm, wherein the encapsulation material of the microcapsule is a mixture of melamine, formaldehyde and urea (through the combination of urea and a specific formula, the formaldehyde residue is effectively reduced to avoid affecting the coating performance of the encapsulation material), the phase change core of the microcapsule is paraffin; the matrix material is epoxy resin; the phase change temperature of the phase change material is 95-120°C, and the density is 1.0-1.3 g / cm 3 , the phase change enthalpy value is 220-260 J / g. The mass ratio between the epoxy resin (matrix material) and the microcapsule (phase change raw material) is 1:1-15; the mass ratio between the microcapsule encapsulation material (i.e. melamine formaldehyde resin) and paraffin is 6:1; the mass ratio of melamine and formaldehyde urea in the encapsulation material is 10:20-30:1-5.

[0012] Based on further optimization of the above solution, the thickness of the cold surface protection layer is 0.03-0.1 mm, and the cold surface protection layer is a flat and smooth metal titanium foil, which is convenient for installation of the cold surface protection layer.

[0013] Based on further optimization of the above scheme, the hot surface protection layer and the cold surface protection layer in step 2 are cleaned and dried with ethyl acetate before use. The welding process requirements in step 2 are: 1 to 3 rows of welding, the welding point spacing is 6±2mm, and the welding point indentation diameter is 1±0.5mm.

[0014] Based on the further optimization of the above scheme, the multiple coating process of the anti-ablative layer is specifically as follows: the thickness of the anti-ablative layer is K, and it is divided into N times of coating, and the thickness of each coating is K / N. At the same time, after each layer is coated, it is dried and cured as required to ensure that the next layer can be constructed only after the previous layer is completely cured; the multiple coating process can effectively prevent the anti-ablative layer from bulging, thereby avoiding problems such as pores and cracks during the expansion and carbonization process. During the coating of the anti-ablative layer and the transition layer, the construction environment temperature is 5-40°C, the component surface temperature is 5-45°C, the air humidity during the coating process is not more than 90%, and the air circulation at the coating site is maintained and the wind speed is not more than 5m / s.

[0015] The following are the effects of the technical solution of the present invention: The present invention achieves the purpose of flame blocking and heat insulation by adopting a dense carbonized layer formed by the anti-ablation layer of the intumescent fire retardant coating when it expands and carbonizes when it encounters heat. The cooperation between the hot surface protection layer, the transition layer and the anti-ablation layer can not only reflect and block thermal radiation to achieve fire prevention and heat insulation, but also effectively enhance the interlayer bonding strength, provide a buffer for the expansion and carbonization process, and avoid cracking, falling off and other problems in the anti-ablation layer during the expansion and carbonization process. Through the coordination between the heat insulation layer and the heat-resistance layer, the synergistic effect of phase change heat absorption and aerogel felt insulation is used to achieve heat insulation, and the heat insulation effect is improved while ensuring light weight and thin thickness; the coordination between the hot surface protection layer, the heat insulation layer, the heat-resistance layer and the cold surface protection layer is used to not only achieve the solid positioning and protection of the heat insulation layer and the heat-resistance layer, and avoid problems such as falling off, offset, and cracking between them (i.e., the heat insulation layer and the heat-resistance layer), but also form a large number of cavity matrices to inhibit and partition heat conduction and dissipate, avoid the formation of temperature convergence points, and further improve the efficiency and effect of heat insulation. In addition, it can effectively avoid the appearance of gaps between composite materials and structural parts, and ensure the stability of composite material coating and fireproof insulation. The hot surface protection layer and the cold surface protection layer can also improve the overall resistance to infiltration and corrosion of the composite material, thereby ensuring that each layer fully plays its role. The composite material prepared by the method of the present invention not only has the characteristics of excellent fireproof and heat-insulating performance, thin thickness, light weight, etc., but also has the advantages of simple structure, convenient installation, wide application range, etc., and can be used for fireproof and heat-insulating of hot end components of various equipment in high temperature environments of 400°C to 1200°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Schematic diagram of the thermal insulation composite material in an embodiment of the present invention.

[0017] Figure 2 Schematic diagram of the structure of the hot surface protection layer of the thermal insulation composite material in an embodiment of the present invention.

[0018] Among them, 10, anti-ablation layer; 20, transition layer; 30, hot surface protection layer; 40, thermal insulation layer; 50, heat resistance layer; 60, cold surface protection layer. DETAILED DESCRIPTION

[0019] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments and drawings. The contents mentioned in the implementation modes are not intended to limit the present invention.

[0020] Embodiment 1: A method for preparing a composite thermal insulation material, see Figure 1 As shown, the thermal insulation composite material comprises an anti-ablation layer 10, a transition layer 20, a hot surface protection layer 30, a heat insulation layer 40, a heat-resistant layer 50 and a cold surface protection layer 60 in sequence; wherein the thickness of the anti-ablation layer 10 is 0.6 mm; the anti-ablation layer 10 adopts an intumescent fire retardant coating, and the intumescent fire retardant coating comprises a film-forming material, a flame retardant and a functional filler, and the mass ratio of the film-forming material, the flame retardant and the functional filler is 2:6:1; wherein the film-forming material is a high elastic polyurethane polymer (wherein the high elastic The polyurethane polymer is polymerized by one or two of polycaprolactone diol and polyether diol and aliphatic polyisocyanate HDI); the flame retardant is composed of ammonium polyphosphate, pentaerythritol and melamine, and the mass ratio between them is 5:4:2; the functional filler is composed of nano-aluminum hydroxide, expanded graphite and ultrafine ceramic hollow microspheres (the average particle size of the ultrafine ceramic hollow microspheres is 20μm, and the melting point is not less than 1600℃), and the mass ratio between them is 5:2:3.

[0021] The thickness of the transition layer 20 is 40 μm, and the transition layer 20 uses epoxy primer. The thickness of the hot surface protection layer 30 (when the hot surface protection layer 30 is flat) is 0.03 mm; the hot surface protection layer 30 uses a metal embossed titanium foil structure, that is, protrusions distributed in an array are arranged on the surface of the flat titanium foil structure (refer to Figure 2 As shown, the protrusions of the heat surface protection layer 30 are oriented toward the transition layer 20); the shape of the protrusions is rice grain-like; the diameter of the protrusions is 1 mm and the height is 0.4 mm; the distance between two adjacent protrusions is 4 mm; the number of protrusions per unit area in the heat surface protection layer 30 is 6x10 4 indivual.

[0022] The thickness of the heat insulation layer 40 is 2 mm, and the heat insulation layer 40 adopts basalt fiber reinforced silica aerogel felt; wherein, the diameter of the basalt fiber is not greater than 6 μm, the mass ratio of basalt fiber to silica aerogel is 1:0.78, and the thermal conductivity of the basalt fiber reinforced silica aerogel felt at room temperature is 0.020 W / (m•K); the volume density of the basalt fiber reinforced silica aerogel felt is 159.74 kg / m 3 The bulk density of the preform formed by basalt fiber is 89.74kg / m 3 The density of silica aerogel is 70kg / m 3 The thickness of the heat-resistant layer 50 is 2 mm. The heat-resistant layer 50 adopts phase change material, which is composed of a phase change raw material and a matrix material. The phase change raw material is a microcapsule, and the average particle size of the microcapsule is 30 μm. The encapsulation material of the microcapsule is a mixture of melamine, formaldehyde and urea, and the mass ratio of melamine, formaldehyde and urea in the encapsulation material is 10:20:1. The phase change core of the microcapsule is paraffin, and the mass ratio between the encapsulation material (i.e., melamine formaldehyde resin) and the paraffin is 6:1. The matrix material is epoxy resin, and the mass ratio between epoxy resin (matrix material) and microcapsule (phase change raw material) is 1:2. The phase change temperature of the phase change material is 95°C, and the density is 1.0 g / cm 3 , phase change enthalpy value is 220 J / g. The thickness of the cold surface protection layer 60 is 0.03 mm, and the cold surface protection layer 60 is a flat and smooth metal titanium foil.

[0023] The specific preparation method is: Step 1: Prepare the coatings of the anti-ablation layer 10 and the transition layer 20 as needed (i.e., the raw materials of the anti-ablation layer 10 are uniformly mixed according to the above formula to obtain the coating of the anti-ablation layer 10, and the coating of the transition layer 20 can be an existing product in the art) and the blanks of the hot surface protection layer 30, the heat insulation layer 40, the heat barrier layer 50, and the cold surface protection layer 60 (the hot surface protection layer 30 is prepared by embossing the existing flat and smooth titanium foil with the thickness size in accordance with the above size; the heat insulation layer 40 is prepared by the basalt fiber reinforced silica aerogel according to the above ratio of basalt fiber and silica aerogel The preparation method of the silicon aerogel felt can adopt the existing preparation method of the fiber reinforced aerogel felt; the heat-resistant layer 50 is prepared by uniformly mixing the materials in the above-mentioned proportion; the cold surface protection layer 60 can adopt the titanium foil of the existing composite thickness size), and the blanks are cut (that is, the blanks of the hot surface protection layer 30, the thermal insulation layer 40, the thermal insulation layer 50, and the cold surface protection layer 60 are cut according to the size of the thermal insulation coating required for the component and the required thickness of the thermal insulation layer 40 and the thermal insulation layer 50, and the cutting method is conventional in the art and is not specifically limited in this embodiment).

[0024] Step 2: The hot surface protection layer 30 and the cold surface protection layer 60 are cleaned and dried with ethyl acetate before use; the hot surface protection layer 30 is placed on a workbench plane (specifically: the raised side of the hot surface protection layer 30 is placed downward), and the heat insulation layer 40 and the heat resistance layer 50 are sequentially attached to the end surface of the hot surface protection layer 30; then, the weldment consisting of the hot surface protection layer 30, the heat insulation layer 40 and the heat resistance layer 50 is embedded in the cold surface protection layer 60 (if there is too much edge material and it cannot be embedded, the outer edge of the cold surface protection layer 60 can be appropriately trimmed), and then the outer circle of the hot surface protection layer 30 is folded inward to form a weldment for the cold surface protection layer 60. 0 coating (after folding, hammer can be used to knock the folded part to ensure tightness); finally, check whether there are any misalignment, abnormal bulging, etc. in the hot surface protection layer 30, the heat insulation layer 40, the heat resistance layer 50, and the cold surface protection layer 60. If there is no abnormality, weld them (i.e., between the hot surface protection layer 30 and the cold surface protection layer 60). The welding process requirements are: single-row welding, welding point spacing 6±2mm, welding point indentation diameter 1±0.5mm; before starting the welding machine each time, select 5 points of the sample with the same structure and thickness for trial welding, and formally weld after passing the tear test. Grind and remove burrs on the edges of the hot surface protection layer 30 and the cold surface protection layer 60 after welding.

[0025] Step 3: First, apply the transition layer 20 on the surface of the hot surface protection layer 30 (i.e., the side away from the insulation layer 40). Then, the anti-ablation layer 10 is applied on the surface of the transition layer 20 by multiple brushing processes. The multiple brushing processes of the anti-ablation layer 10 are as follows: the thickness of the anti-ablation layer 10 is 0.6 mm, and it is applied 6 times, and the thickness of each brushing is 0.1 mm. At the same time, after each layer is applied, it is dried and cured as required to ensure that the next layer can be constructed only after the previous layer is completely cured; wherein, during the application of the anti-ablation layer 10 and the transition layer 20, the construction environment temperature is 15°C, the surface temperature of the component is 20°C, the air humidity during the application process is not more than 90%, and the air circulation at the application site is maintained and the wind speed is not more than 5m / s. Finally, a thermal insulation composite material is obtained.

[0026] Embodiment 2: A method for preparing a composite thermal insulation material, see Figure 1As shown, the thermal insulation composite material comprises an anti-ablation layer 10, a transition layer 20, a hot surface protection layer 30, a heat insulation layer 40, a heat-resistant layer 50 and a cold surface protection layer 60 in sequence; wherein the thickness of the anti-ablation layer 10 is 0.8 mm; the anti-ablation layer 10 adopts an intumescent fire retardant coating, and the intumescent fire retardant coating comprises a film-forming material, a flame retardant and a functional filler, and the mass ratio of the film-forming material, the flame retardant and the functional filler is 2.5:8:2; wherein the film-forming material is a high elastic polyurethane polymer (wherein, high The elastic polyurethane polymer is polymerized by one or two of polycaprolactone diol and polyether diol and aliphatic polyisocyanate HDI); the flame retardant is composed of ammonium polyphosphate, pentaerythritol and melamine, and the mass ratio between them is 6:5:3; the functional filler is composed of nano-aluminum hydroxide, expanded graphite and ultrafine ceramic hollow microspheres (the average particle size of the ultrafine ceramic hollow microspheres is 35μm, and the melting point is not less than 1600℃), and the mass ratio between them is 8:3:5.

[0027] The thickness of the transition layer 20 is 50 μm, and the transition layer 20 uses epoxy primer. The thickness of the hot surface protection layer 30 (when the hot surface protection layer 30 is flat) is 0.06 mm; the hot surface protection layer 30 uses a metal embossed titanium foil structure, that is, protrusions distributed in an array are arranged on the surface of the flat titanium foil structure (refer to Figure 2 As shown, the protrusions of the heat surface protection layer 30 are oriented toward the transition layer 20); the shape of the protrusions is pearl-shaped; the diameter of the protrusions is 1.5 mm and the height is 0.7 mm; the distance between two adjacent protrusions is 6 mm; the number of protrusions per unit area in the heat surface protection layer 30 is 3.5x10 4 indivual.

[0028] The thickness of the heat insulation layer 40 is 3 mm, and the heat insulation layer 40 is made of basalt fiber reinforced silica aerogel felt; wherein the diameter of the basalt fiber is not greater than 6 μm, the mass ratio of basalt fiber to silica aerogel is 1:0.85, and the thermal conductivity of the basalt fiber reinforced silica aerogel felt at room temperature is 0.018 W / (m•K); the volume density of the basalt fiber reinforced silica aerogel felt is 163.24 kg / m 3 The bulk density of the preform formed by basalt fiber is 88.24kg / m 3 The density of silica aerogel is 75kg / m 3The thickness of the heat-resistant layer 50 is 3 mm. The heat-resistant layer 50 adopts phase change material, which is composed of a phase change raw material and a matrix material. The phase change raw material is a microcapsule, and the average particle size of the microcapsule is 60 μm. The encapsulation material of the microcapsule is a mixture of melamine, formaldehyde and urea, and the mass ratio of melamine, formaldehyde and urea in the encapsulation material is 10:25:3. The phase change core of the microcapsule is paraffin, and the mass ratio between the encapsulation material (i.e., melamine formaldehyde resin) and the paraffin is 6:1. The matrix material is epoxy resin, and the mass ratio between epoxy resin (matrix material) and microcapsule (phase change raw material) is 1:6. The phase change temperature of the phase change material is 110°C, and the density is 1.2 g / cm 3 , the phase change enthalpy value is 240 J / g. The thickness of the cold surface protection layer 60 is 0.06 mm, and the cold surface protection layer 60 is a flat and smooth metal titanium foil.

[0029] The specific preparation method is: Step 1: Prepare the coatings of the anti-ablation layer 10 and the transition layer 20 as needed (i.e., the raw materials of the anti-ablation layer 10 are uniformly mixed according to the above formula to obtain the coating of the anti-ablation layer 10, and the coating of the transition layer 20 can be an existing product in the art) and the blanks of the hot surface protection layer 30, the heat insulation layer 40, the heat barrier layer 50, and the cold surface protection layer 60 (the hot surface protection layer 30 is prepared by embossing the existing flat and smooth titanium foil with the thickness size in accordance with the above size; the heat insulation layer 40 is prepared by the basalt fiber reinforced silica aerogel according to the above ratio of basalt fiber and silica aerogel The preparation method of the silicon aerogel felt can adopt the existing preparation method of the fiber reinforced aerogel felt; the heat-resistant layer 50 is prepared by uniformly mixing the materials in the above-mentioned proportion; the cold surface protection layer 60 can adopt the titanium foil of the existing composite thickness size), and the blanks are cut (that is, the blanks of the hot surface protection layer 30, the thermal insulation layer 40, the thermal insulation layer 50, and the cold surface protection layer 60 are cut according to the size of the thermal insulation coating required for the component and the required thickness of the thermal insulation layer 40 and the thermal insulation layer 50, and the cutting method is conventional in the art and is not specifically limited in this embodiment).

[0030] Step 2: The hot surface protection layer 30 and the cold surface protection layer 60 are cleaned and dried with ethyl acetate before use; the hot surface protection layer 30 is placed on a workbench plane (specifically: the raised side of the hot surface protection layer 30 is placed downward), and the heat insulation layer 40 and the heat resistance layer 50 are sequentially attached to the end surface of the hot surface protection layer 30; then, the weldment consisting of the hot surface protection layer 30, the heat insulation layer 40 and the heat resistance layer 50 is embedded in the cold surface protection layer 60 (if there is too much edge material and it cannot be embedded, the outer edge of the cold surface protection layer 60 can be appropriately trimmed), and then the outer circle of the hot surface protection layer 30 is folded inward to form a weldment for the cold surface protection layer 60 (After folding, hammer can be used to knock the folded part to ensure tightness of the fit); finally, check whether there are any problems such as misalignment, abnormal bulging, etc. in the hot surface protection layer 30, the heat insulation layer 40, the heat resistance layer 50, and the cold surface protection layer 60. If there is no abnormality, weld them (i.e., between the hot surface protection layer 30 and the cold surface protection layer 60). The welding process requirements are: double-row staggered welding, welding point spacing 6±2mm, welding point indentation diameter 1±0.5mm; before starting the welding machine each time, select 5 points of the sample with the same structure and thickness for trial welding, and formally weld after passing the tear test. Grind and remove burrs on the edges of the hot surface protection layer 30 and the cold surface protection layer 60 after welding.

[0031] Step 3: First, apply the transition layer 20 on the surface of the hot surface protection layer 30 (i.e., the side away from the insulation layer 40). Then, the anti-ablation layer 10 is applied on the surface of the transition layer 20 by multiple brushing processes. The multiple brushing processes of the anti-ablation layer 10 are as follows: the thickness of the anti-ablation layer 10 is 0.8 mm, and it is applied 8 times, and the thickness of each brushing is 0.1 mm. At the same time, after each layer is applied, it is dried and cured as required to ensure that the next layer can be constructed only after the previous layer is completely cured; wherein, during the application of the anti-ablation layer 10 and the transition layer 20, the construction environment temperature is 25°C, the surface temperature of the component is 30°C, the air humidity during the application process is not more than 90%, and the air circulation at the application site is maintained and the wind speed is not more than 5m / s. Finally, a thermal insulation composite material is obtained.

[0032] Embodiment 3: A method for preparing a composite thermal insulation material, see Figure 1As shown, the thermal insulation composite material comprises an anti-ablation layer 10, a transition layer 20, a hot surface protection layer 30, a heat insulation layer 40, a heat-resistant layer 50 and a cold surface protection layer 60 in sequence; wherein the thickness of the anti-ablation layer 10 is 1.0 mm; the anti-ablation layer 10 adopts an intumescent fire retardant coating, and the intumescent fire retardant coating comprises a film-forming material, a flame retardant and a functional filler, and the mass ratio of the film-forming material, the flame retardant and the functional filler is 3:10:3; wherein the film-forming material is a high elastic polyurethane polymer (wherein the high elastic The polyurethane polymer is polymerized by one or two of polycaprolactone diol and polyether diol and aliphatic polyisocyanate HDI); the flame retardant is composed of ammonium polyphosphate, pentaerythritol and melamine, and the mass ratio between them is 8:7:4; the functional filler is composed of nano-aluminum hydroxide, expanded graphite and ultrafine ceramic hollow microspheres (the average particle size of the ultrafine ceramic hollow microspheres is 50μm, and the melting point is not less than 1600℃), and the mass ratio between them is 10:5:8.

[0033] The thickness of the transition layer 20 is 60 μm, and the transition layer 20 uses epoxy primer. The thickness of the hot surface protection layer 30 (when the hot surface protection layer 30 is flat) is 0.1 mm; the hot surface protection layer 30 uses a metal embossed titanium foil structure, that is, protrusions distributed in an array are arranged on the surface of the flat titanium foil structure (refer to Figure 2 As shown, the protrusion direction of the hot surface protection layer 30 is toward the transition layer 20); the shape of the protrusion is a water drop shape; the diameter of the protrusion is 2.5mm and the height is 1.0mm; the distance between two adjacent protrusions is 8mm; the number of protrusions per unit area in the hot surface protection layer 30 is 1.5x10 4 indivual.

[0034] The thickness of the heat insulation layer 40 is 5 mm, and the heat insulation layer 40 adopts basalt fiber reinforced silica aerogel felt; wherein, the diameter of the basalt fiber is not greater than 6 μm, the mass ratio of basalt fiber to silica aerogel is 1:1, and the thermal conductivity of the basalt fiber reinforced silica aerogel felt at room temperature is 0.017 W / (m•K); the volume density of the basalt fiber reinforced silica aerogel felt is 160 kg / m 3 The bulk density of the preform formed by basalt fiber is 80kg / m 3 , the density of silica aerogel is 80kg / m 3The thickness of the heat-resistant layer 50 is 5 mm. The heat-resistant layer 50 adopts phase change material, which is composed of a phase change raw material and a matrix material. The phase change raw material is a microcapsule, and the average particle size of the microcapsule is 70 μm. The encapsulation material of the microcapsule is a mixture of melamine, formaldehyde and urea, and the mass ratio of melamine, formaldehyde and urea in the encapsulation material is 10:30:5. The phase change core of the microcapsule is paraffin, and the mass ratio between the encapsulation material (i.e., melamine formaldehyde resin) and the paraffin is 6:1. The matrix material is epoxy resin, and the mass ratio between epoxy resin (matrix material) and microcapsule (phase change raw material) is 1:8. The phase change temperature of the phase change material is 120°C, and the density is 1.3 g / cm 3 , the phase change enthalpy value is 260 J / g. The thickness of the cold surface protection layer 60 is 0.1 mm, and the cold surface protection layer 60 is a flat and smooth metal titanium foil.

[0035] The specific preparation method is: Step 1: Prepare the coatings of the anti-ablation layer 10 and the transition layer 20 as needed (i.e., the raw materials of the anti-ablation layer 10 are uniformly mixed according to the above formula to obtain the coating of the anti-ablation layer 10, and the coating of the transition layer 20 can be an existing product in the art) and the blanks of the hot surface protection layer 30, the heat insulation layer 40, the heat barrier layer 50, and the cold surface protection layer 60 (the hot surface protection layer 30 is prepared by embossing the existing flat and smooth titanium foil with the thickness size in accordance with the above size; the heat insulation layer 40 is prepared by the basalt fiber reinforced silica aerogel according to the above ratio of basalt fiber and silica aerogel The preparation method of the silicon aerogel felt can adopt the existing preparation method of the fiber reinforced aerogel felt; the heat-resistant layer 50 is prepared by uniformly mixing the materials in the above-mentioned proportion; the cold surface protection layer 60 can adopt the titanium foil of the existing composite thickness size), and the blanks are cut (that is, the blanks of the hot surface protection layer 30, the thermal insulation layer 40, the thermal insulation layer 50, and the cold surface protection layer 60 are cut according to the size of the thermal insulation coating required for the component and the required thickness of the thermal insulation layer 40 and the thermal insulation layer 50, and the cutting method is conventional in the art and is not specifically limited in this embodiment).

[0036] Step 2: The hot surface protection layer 30 and the cold surface protection layer 60 are cleaned and dried with ethyl acetate before use; the hot surface protection layer 30 is placed on a workbench plane (specifically: the raised side of the hot surface protection layer 30 is placed downward), and the heat insulation layer 40 and the heat resistance layer 50 are sequentially attached to the end surface of the hot surface protection layer 30; then, the weldment consisting of the hot surface protection layer 30, the heat insulation layer 40 and the heat resistance layer 50 is embedded in the cold surface protection layer 60 (if there is too much edge material and it cannot be embedded, the outer edge of the cold surface protection layer 60 can be appropriately trimmed), and then the outer circle of the hot surface protection layer 30 is folded inward to form a weldment for the cold surface protection layer 60 (After folding, hammer can be used to knock the folded part to ensure tightness of the fit); finally, check whether there are any problems such as misalignment, abnormal bulging, etc. in the hot surface protection layer 30, the heat insulation layer 40, the heat resistance layer 50, and the cold surface protection layer 60. If there is no abnormality, weld them (i.e., between the hot surface protection layer 30 and the cold surface protection layer 60). The welding process requirements are: use 3 rows of staggered welding, the welding point spacing is 6±2mm, and the welding point indentation diameter is 1±0.5mm; before starting the welding machine each time, select 5 points of the sample with the same structure and thickness for trial welding, and formally weld after passing the tear test. Grind and remove burrs on the edges of the hot surface protection layer 30 and the cold surface protection layer 60 after welding.

[0037] Step 3: First, apply the transition layer 20 on the surface of the hot surface protection layer 30 (i.e., the side away from the insulation layer 40). Then, the anti-ablation layer 10 is applied on the surface of the transition layer 20 by multiple brushing processes. The multiple brushing processes of the anti-ablation layer 10 are as follows: the thickness of the anti-ablation layer 10 is 1.0 mm, and it is applied 5 times, and the thickness of each brushing is 0.2 mm. At the same time, after each layer is applied, it is dried and cured as required to ensure that the next layer can be constructed only after the previous layer is completely cured; wherein, during the application of the anti-ablation layer 10 and the transition layer 20, the construction environment temperature is 35°C, the surface temperature of the component is 40°C, the air humidity during the application process is not more than 90%, and the air circulation at the application site is maintained and the wind speed is not more than 5 m / s. Finally, a thermal insulation composite material is obtained.

[0038] Comparative Example 1: A thermal insulation composite material, which comprises an anti-ablation layer, a transition layer, a hot surface protection layer, a thermal insulation layer, a heat-resistant layer and a cold surface protection layer in sequence; wherein the thickness and material of the anti-ablation layer, the transition layer, the thermal insulation layer, the heat-resistant layer and the cold surface protection layer are consistent with those in Example 2, the hot surface protection layer has a thickness of 0.06 mm, and the hot surface protection layer adopts a flat and smooth metal titanium foil.

[0039] The preparation method of the above-mentioned thermal insulation composite material is substantially the same as the preparation method in Example 2, except that when obtaining the blank of the hot surface protection layer in step 1, a smooth titanium foil with existing composite thickness requirements is directly used.

[0040] Comparative Example 2: A thermal insulation composite material, which comprises an anti-ablation layer, a transition layer, a hot surface protection layer, a first thermal resistance layer and a cold surface protection layer in sequence; wherein the thickness and material of the ablation layer, the transition layer, the hot surface protection layer and the cold surface protection layer are consistent with those in Example 2; the thickness of the first thermal resistance layer is 6 mm, the first thermal resistance layer adopts basalt fiber reinforced silica aerogel felt, the diameter of the basalt fiber is not more than 6 μm, the mass ratio of basalt fiber to silica aerogel is 1:0.85, and the thermal conductivity of the basalt fiber reinforced silica aerogel felt at room temperature is 0.018 W / (m•K); the volume density of the basalt fiber reinforced silica aerogel felt is 163.24 kg / m 3 The bulk density of the preform formed by basalt fiber is 88.24kg / m 3 The density of silica aerogel is 75kg / m 3 .

[0041] The preparation method of the above-mentioned thermal insulation composite material is generally consistent with the preparation method in Example 2, except that: in step 1, only the blank of the first thermal resistance layer is blanked, and the blank of the thermal insulation layer 40 and the thermal resistance layer 50 is not blanked; during compounding in step 2, only the first thermal resistance layer is stacked between the hot surface protection layer and the cold surface protection layer.

[0042] Comparative Example 3: A thermal insulation composite material, which comprises an anti-ablation layer, a transition layer, a hot surface protection layer, a second thermal resistance layer and a cold surface protection layer in sequence; wherein the thickness and material of the ablation layer, the transition layer, the hot surface protection layer and the cold surface protection layer are consistent with those in Example 2; the thickness of the second thermal resistance layer is 6 mm; the second thermal resistance layer adopts a phase change material, the phase change material is composited by a phase change raw material and a matrix material, the phase change raw material is a microcapsule, and the average particle size of the microcapsule is 60 μm, wherein the encapsulation material of the microcapsule is a mixture of melamine, formaldehyde and urea, and the mass ratio of melamine, formaldehyde and urea in the encapsulation material is 10:25:3; the phase change core of the microcapsule is paraffin, and the mass ratio between the encapsulation material (i.e., melamine formaldehyde resin) and the paraffin is 6:1; the matrix material is epoxy resin, and the mass ratio between the epoxy resin (matrix material) and the microcapsule (phase change raw material) is 1:6; the phase change temperature of the phase change material is 110°C, and the density is 1.2 g / cm 3 , phase change enthalpy is 240J / g.

[0043] The preparation method of the above-mentioned thermal insulation composite material is generally consistent with the preparation method in Example 2, except that: in step one, only the blank of the second thermal resistance layer is blanked, and the blank of the thermal insulation layer 40 and the thermal resistance layer 50 is not blanked; during compounding in step two, only the second thermal resistance layer is stacked between the hot surface protection layer and the cold surface protection layer.

[0044] Comparative Example 4: A method for preparing a composite thermal insulation material, the thermal insulation composite material sequentially comprising an anti-ablation layer, a transition layer, a hot surface protection layer, a thermal insulation layer, a heat-resistant layer and a cold surface protection layer; wherein the thickness and material of the transition layer, the hot surface protection layer, the thermal insulation layer, the heat-resistant layer and the cold surface protection layer are consistent with those in Example 2; the thickness of the anti-ablation layer is 0.8 mm; an intumescent fire retardant coating is used, the intumescent fire retardant coating comprises a film former, a flame retardant and a functional filler, and the mass ratio of the film former, the flame retardant and the functional filler is 2.5:8:2; Among them, the film-forming material is a high-elastic polyurethane polymer (wherein the high-elastic polyurethane polymer is polymerized by one or two of polycaprolactone diol, polyether diol and aliphatic polyisocyanate HDI); the flame retardant is composed of ammonium polyphosphate, pentaerythritol and melamine, and the mass ratio between them is 6:5:3; the functional filler is composed of expanded graphite and ultrafine ceramic hollow microspheres (the average particle size of the ultrafine ceramic hollow microspheres is 35μm, and the melting point is not lower than 1600℃), and the mass ratio between them is 3:5.

[0045] The preparation method of the above thermal insulation composite material is substantially the same as the preparation method in Example 2, except that: in the preparation process of the anti-ablation layer coating in step 1, the functional filler of nano-aluminum hydroxide is not added.

[0046] The thermal insulation composite material samples in Examples 1 to 3 and Comparative Examples 1 to 4 were fixed on the tooling of the inner cavity of the heating equipment, and three thermocouples were arranged on the cold surface of the sample and evenly distributed on the cold surface of the sample. When the ambient temperature was 25 degrees Celsius (the other test conditions were also the same) and the hot surface temperature was 800°C, the cold surface temperature of the corresponding sample was obtained, and the test time was 300s. The test results are as follows:

[0047] As shown in the table above: the structural combination of the specific anti-ablation layer, transition layer, hot surface protection layer, thermal insulation layer, heat-resistant layer, and cold surface protection layer of the present application, in combination with the specific material combination of the corresponding structural layer, can effectively improve the fireproof and heat-insulating properties of the composite material. Under the action of a hot surface temperature of 800°C for a long time (i.e., 300s), the average cold surface temperature of the thermal insulation composite material prepared by the present application is not greater than 60°C, which is significantly lower than that of the composite materials prepared in Comparative Examples 1 to 4. At the same time, the temperature difference of each temperature measuring point of the composite material prepared by the present application is small, which proves that the structure of the present application can dissipate heat evenly without temperature concentration points, while the temperature deviation of the temperature measuring points of the composite materials in Comparative Examples 1 to 4 is large, which also indirectly proves that the interlayer heat insulation effect of the present application is good.

Claims

1. A method for preparing a composite thermal insulation material, characterized in that: The thermal insulation composite material comprises an anti-ablation layer, a transition layer, a hot surface protection layer, a heat insulation layer, a heat-resistant layer and a cold surface protection layer in sequence; the anti-ablation layer adopts an intumescent fire retardant coating, the transition layer adopts a primer, the hot surface protection layer and the cold surface protection layer adopt metal titanium foil, the heat insulation layer adopts an aerogel felt, and the heat-resistant layer adopts a phase change material; The thickness of the heat-resistant layer is 2 to 5 mm; the phase change material is composed of a phase change raw material and a matrix material, the phase change raw material is a microcapsule, the particle size of the microcapsule is 10 to 100 μm, wherein the encapsulation material of the microcapsule is a mixture of melamine, formaldehyde and urea, and the phase change core of the microcapsule is paraffin; the matrix material is epoxy resin; the phase change temperature of the phase change material is 95 to 120°C, and the density is 1.0 to 1.3 g / cm 3 , phase change enthalpy value 220~260J / g; The specific preparation method is as follows: step 1, prepare coatings for the anti-ablation layer and transition layer and blanks for the hot surface protection layer, thermal insulation layer, heat resistance layer and cold surface protection layer as needed, and cut the blanks; step 2, place the hot surface protection layer on a workbench plane, and sequentially attach the thermal insulation layer and the heat resistance layer to the end face of the hot surface protection layer; then, embed the weldment consisting of the hot surface protection layer, the thermal insulation layer and the heat resistance layer into the cold surface protection layer, and then fold the outer circle of the hot surface protection layer inward to form a coating for the cold surface protection layer, and weld their joints; step 3, first apply a transition layer on the surface of the hot surface protection layer; then, use a multiple coating process to apply the anti-ablation layer on the surface of the transition layer to obtain a thermal insulation composite material.

2. The method for preparing a composite thermal insulation material according to claim 1, characterized in that: The thickness of the anti-ablation layer is 0.6-1.0 mm; the intumescent fire retardant coating comprises a film former, a flame retardant and a functional filler, and the mass ratio of the film former, the flame retardant and the functional filler is 2-3:6-10:1-3; wherein the film former is a high-elastic polyurethane polymer; the flame retardant is composed of ammonium polyphosphate, pentaerythritol and melamine, and the mass ratio thereof is 5-8:4-7:2-4; the functional filler is composed of nano-grade aluminum hydroxide, expanded graphite and ultrafine ceramic hollow microspheres, and the mass ratio thereof is 5-10:2-5:3-8.

3. The method for preparing a composite thermal insulation material according to claim 1 or 2, characterized in that: The thickness of the transition layer is 40-60 μm, and the transition layer adopts epoxy primer.

4. The method for preparing a composite thermal insulation material according to claim 1 or 3, characterized in that: The thickness of the hot surface protection layer is 0.03-0.1 mm. The hot surface protection layer adopts a metal embossed titanium foil structure, that is, protrusions distributed in an array are arranged on the surface of the flat titanium foil structure. The shape of the protrusions is any one of rice grains, pearls, and water drops.

5. The method for preparing a composite thermal insulation material according to claim 1 or 3, characterized in that: The thickness of the thermal insulation layer is 2 to 5 mm, and the thermal insulation layer is made of basalt fiber reinforced silica aerogel felt; wherein the diameter of the basalt fiber is not greater than 6 μm, the mass ratio of basalt fiber to silica aerogel is 1:0.78 to 1, and the thermal conductivity of the basalt fiber reinforced silica aerogel felt at room temperature is 0.017 to 0.020 W / (m•K).

6. The method for preparing a composite thermal insulation material according to claim 5, characterized in that: The volume density of the basalt fiber reinforced silica aerogel felt is 150-170 kg / m 3 The bulk density of the preform formed by basalt fiber is 80~90kg / m 3 The density of silica aerogel is 70~80kg / m 3 .

7. The method for preparing a composite thermal insulation material according to claim 1, characterized in that: The mass ratio between the epoxy resin and the microcapsules is 1:1-15; the mass ratio between the microcapsule encapsulation material and paraffin is 6:1; and the mass ratio between melamine and formaldehyde urea in the encapsulation material is 10:20-30:1-5.

8. The method for preparing a composite thermal insulation material according to claim 1 or 3, characterized in that: The thickness of the cold surface protection layer is 0.03-0.1 mm, and the cold surface protection layer is a flat and smooth metal titanium foil.

9. The method for preparing a composite thermal insulation material according to claim 1, characterized in that: In the step 2, the hot surface protection layer and the cold surface protection layer are cleaned and dried with ethyl acetate before use; the welding process requirements in step 2 are: using 1 to 3 rows of welding, the welding point spacing is 6±2mm, and the welding point indentation diameter is 1±0.5mm.

10. The method for preparing a composite thermal insulation material according to claim 1, characterized in that: The multiple coating process of the anti-ablation layer is specifically as follows: the thickness of the anti-ablation layer is K, and it is coated N times, and the thickness of each coating is K / N. At the same time, after each layer is coated, it is dried and cured as required to ensure that the next layer can be constructed only after the previous layer is completely cured.

Citation Information

Patent Citations

  • Phase-change composite thermal-protection layer

    CN108582922A

  • Thermal protection structure of high-speed aircraft

    CN111470029A

  • Flame-retardant heat-insulating composite material and preparation method thereof

    CN116786389A

  • Variable phase-change temperature coating as well as preparation method and application thereof

    CN117186715A

  • Fireproof cover and checking method thereof

    CN118149148A